Contribuição para a análise de vigas mistas de madeira laminada colada e concreto (MLC/Concreto) - Ana Lucia Crespo Oliveira (2002)
This work presents a contribution to the design of glulam and concrete mixed beams subject to pure bending loading. The main purpose of this work is to perform complementar analysis about recent laboratory tests of glulam/concrete mixed beams which has been developed at Laboratório de Análises Experimentais de Estruturas of Universidade Federal de Minas Gerais. By the proposed design specification in thiswork, a glulam/concrete mixed beam and another two wood/concrete composite beam have been analized. All of them have been previously experimentaly analized by brazilian researchers. A post critical review of the international and national literature made possible the adoption of the procedure included in European Standard, EUROCODE 5, part 1-1/1994 and EUROCODE 5, part 2/1997, as design model. The brazilian materials and the parameters of the Brazilian and international codes have been taken into account with basic parameters proposed, such as partial safety factors for material properties for ultimate limit states, the secant elastic modulus of concrete, the equation to obtain the effective width of the concrete flange and the equation to obtain the instantaneous slip modulus of the shear connection. The ANSYS program, version 5.7, has been used to perform the numerical analysis. Linear elastostaticanalysis has been considered. The concrete is taken to be an isotropic material and the wood is considered orthotropic. The final results of stresses and displacements obtained by ANSYS and the proposed design specification have been in good agreement with thevalues obtained in the laboratory tests.